Site‐specific ubiquitination of the E3 ligase HOIP regulates apoptosis and immune signaling. (20th November 2020) - Fennell, Lilian M; Gomez Diaz, Carlos; Deszcz, Luiza; Kavirayani, Anoop; Hoffmann, David; Yanagitani, Kota; Schleiffer, Alexander; Mechtler, Karl; Hagelkruys, Astrid; Penninger, Josef; Ikeda, Fumiyo
Abstract: HOIP, the catalytic component of the linear ubiquitin chain assembly complex (LUBAC), is a critical regulator of inflammation. However, how HOIP itself is regulated to control inflammatory responses is unclear. Here, we discover that site‐specific ubiquitination of K784 within human HOIP promotes tumor necrosis factor (TNF)‐induced inflammatory signaling. A HOIP K784R mutant is catalytically active but shows reduced induction of an NF‐κB reporter relative to wild‐type HOIP. HOIP K784 is evolutionarily conserved, equivalent to HOIP K778 in mice. We generated Hoip K778R/K778R knock‐in mice, which show no overt developmental phenotypes; however, in response to TNF, Hoip K778R/K778R mouse embryonic fibroblasts display mildly suppressed NF‐κB activation and increased apoptotic markers. On the other hand, HOIP K778R enhances the TNF‐induced formation of TNFR complex II and an interaction between TNFR complex II and LUBAC. Loss of the LUBAC component SHARPIN leads to embryonic lethality in Hoip K778R/K778R mice, which is rescued by knockout of TNFR1. We propose that site‐specific ubiquitination of HOIP regulates a LUBAC‐dependent switch between survival and apoptosis in TNF signaling. SYNOPSIS: The E3 ligase complex LUBAC generates Met1‐linked linear ubiquitin chains, and regulates inflammation and cell death. Ubiquitination of the LUBAC catalytic component HOIP itself is found to control apoptosis in mammalian cells and TNF‐dependent development and systemic inflammation in mice. Multiple lysine residues of RBR‐type E3 ligase HOIP are modified with linear and mixed‐linkage polyubiquitin chains. Ubiquitination of human HOIP at K784 within the IBR domain controls the apoptotic pathway in fibroblasts. K784R mutation in HOIP does not affect E3 ligase activity or ability to generate Met1‐linked ubiquitin chains. The equivalent K778R mutation in murine HOIP does not affect mouse development. Synthetic embryonic lethality in SHARPIN‐deficient HOIPK778R/K778R mice is rescued by TNFR1 knockout. Abstract : Ubiquitination of the catalytic subunit of the linear ubiquitin chain assembly complex LUBAC is required for full induction of the NF‐κB pathway and TNF‐induced inflammatory signalling in mice.